2019
DOI: 10.1155/2019/7415212
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen and Oxygen Mixture to Improve Cardiac Dysfunction and Myocardial Pathological Changes Induced by Intermittent Hypoxia in Rats

Abstract: Obstructive sleep apnea (OSA) can cause intermittent changes in blood oxygen saturation, resulting in the generation of many reactive oxygen species (ROS). To discover new antioxidants and clarify the endoplasmic reticulum (ER) stress involved in cardiac injury in OSA, we established a chronic intermittent hypoxia (CIH) rat model with a fraction of inspired O2 (FiO2) ranging from 21% to 9%, 20 times/h for 8 h/day, and the rats were treated with H2-O2 mixture (67% hydrogen and 33% oxygen) for 2 h/day for 35 day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 61 publications
(93 reference statements)
3
41
0
1
Order By: Relevance
“…H 2 can also downregulate ROS directly or as a regulator of a gas-mediated signal. Further, by upregulating the expression of SOD and glutathione (GSH), and downregulating the expression of NADPH oxidase (NOX2) [ 18 ], H 2 can significantly reduce ROS. Another study [ 19 ] showed that H 2 mainly blocks the phosphorylation of ASK1 and its downstream signal molecules p38 MAPK or c-Jun N-terminal kinase (JNK), but not the production of ROS by NADPH oxidase.…”
Section: Mechanisms Of the Action Of Hmentioning
confidence: 99%
See 1 more Smart Citation
“…H 2 can also downregulate ROS directly or as a regulator of a gas-mediated signal. Further, by upregulating the expression of SOD and glutathione (GSH), and downregulating the expression of NADPH oxidase (NOX2) [ 18 ], H 2 can significantly reduce ROS. Another study [ 19 ] showed that H 2 mainly blocks the phosphorylation of ASK1 and its downstream signal molecules p38 MAPK or c-Jun N-terminal kinase (JNK), but not the production of ROS by NADPH oxidase.…”
Section: Mechanisms Of the Action Of Hmentioning
confidence: 99%
“…The accumulation of unfolded protein in the endoplasmic reticulum (ER) caused by pathological stress can trigger ER stress. Zhao et al [ 18 ] observed that hydrogen inhalation significantly reduced the ER stress-related protein and alleviated tissue damage in myocardial I/R injury and later found that a mixture of H 2 and O 2 can block endoplasmic reticulum stress via the PKR-like ER-localized eIF2 α kinase-eukaryotic initiation factor 2 alpha-activating transcription factor 4 (PERK-eIF2 α -ATF 4), inositol-requiring enzyme 1-X-box binding protein 1 (IRE 1-XBP1), and ATF 6 pathways. A study of the relationship between H 2 and ER stress in rats with I/R injury found that H 2 induced the decrease of GRP78 and TNF receptor-associated factor 2 (TRAF2) expression [ 25 ], suggesting that the protective effects of H 2 on myocardial I/R injury are related to decreased ER stress.…”
Section: Mechanisms Of the Action Of Hmentioning
confidence: 99%
“…Evidence have suggested that ATF4/Chop/Bcl-2/Bax signaling pathway is involved in multiple metabolic functions of the body, such as endoplasmic reticulum stress, apoptosis, autophagy, ect ( Yoneshima et al., 2016 ; Liu H. et al., 2020 ; Sharifi et al., 2020 ; Zeng et al., 2020 ). The expression of SOD, GSH-Px, CAT, AE in antioxidant enzymes and the level of ATF4, CHOP, BCL-2, and BAX in ATF4/Chop/Bcl-2/Bax signaling pathways were simultaneously found aberrant expression in endoplasmic reticulum stress and apoptosis ( Gao et al., 2017 ; Xiao et al., 2019 ; Zhao et al., 2019 ; Li et al., 2020 ). Moreover, it was found that NaHS restored the decreased activity of antioxidant enzymes such as GSH, SOD, and CAT in the aging model by regulating to PI3K/AKT signaling pathways ( Chen et al., 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…The total time of intermittent hypoxia was 120 s. The rats had water and food in the cabin and could eat normally. Studies have shown that the method of intermittent hypoxia used in the present study can cause arterial oxygen saturation in rats to fluctuate periodically with the intermittent change of oxygen concentration in the cabin [ 13 ]. The intermittent hypoxia phase of the experiment was conducted daily from 9 am to 5 pm, 8 h/day, and lasted for 6 weeks.…”
Section: Methodsmentioning
confidence: 99%